Improving the accuracy of mandibular reconstruction with vascularized iliac crest flap: Role of computer-assisted techniques. Issue 11 (November 2016) - Zhang, Wen-Bo; Yu, Yao; Wang, Yang; Mao, Chi; Liu, Xiao-Jing; Guo, Chuan-Bin; Yu, Guang-Yan; Peng, Xin
Abstract: While vascularized iliac crest flap is widely used for mandibular reconstruction, it is often challenging to predict the clinical outcome in a conventional operation based solely on the surgeon's experience. Herein, we aimed to improve this procedure by using computer-assisted techniques. We retrospectively reviewed records of 45 patients with mandibular tumor who underwent mandibulectomy and reconstruction with vascularized iliac crest flap from January 2008 to June 2015. Computer-assisted techniques including virtual plan, stereomodel, pre-bending individual reconstruction plate, and surgical navigation were used in 15 patients. The other 30 patients underwent conventional surgery based on the surgeon's experience. Condyle position and reconstructed mandible contour were evaluated based on post-operative computed tomography. Complications were also evaluated during the follow-up. Flap success rate of the patients was 95.6% (43/45). Those in the computer-assisted group presented with better outcomes of the mandibular contour (p = 0.001) and condyle position (p = 0.026). Further, they also experienced beneficial dental restoration (p = 0.011) and postoperative appearance (p = 0.028). The difference between postoperative effect and virtual plan was within the acceptable error margin. There is no significant difference in the incidence of post-operative complications. Thus, computer-assisted techniques can improve the clinical outcomes of mandibular reconstruction with vascularized iliac crest flap.